TAXES AS A SYSTEM-FORMING FACTOR OF SUSTAINABLE DEVELOPMENT OF ECONOMY - Larisa N. Pavlova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article shows the author's opinion on the present situation in the taxation system and exposes the impact of changing the structure of taxes on shaping the revenues of the consolidated budget. The author identifies the reasons for and factors causing the necessary correction of tax coming to the federal budget. Steps aimed at implementation of the government crisis plan were analyzed. Arguments on reforms of the taxation system and their expected effects were put forward. The article compares different points of view concerning the situation in economy and their impact on taxes and budget. The most acute bills were considered. The necessity to raise the status and extend authorities of taxation bodies was substantiated.